Long-Term Improvements After Multimodal Rehabilitation in Late Phase After Stroke: A Randomized Controlled Trial. Issue 7 (July 2017) - Bunketorp-Käll, Lina; Lundgren-Nilsson, Åsa; Samuelsson, Hans; Pekny, Tulen; Blomvé, Karin; Pekna, Marcela; Pekny, Milos; Blomstrand, Christian; Nilsson, Michael
Abstract : Background and Purpose—: Treatments that improve function in late phase after stroke are urgently needed. We assessed whether multimodal interventions based on rhythm-and-music therapy or horse-riding therapy could lead to increased perceived recovery and functional improvement in a mixed population of individuals in late phase after stroke. Methods—: Participants were assigned to rhythm-and-music therapy, horse-riding therapy, or control using concealed randomization, stratified with respect to sex and stroke laterality. Therapy was given twice a week for 12 weeks. The primary outcome was change in participants' perception of stroke recovery as assessed by the Stroke Impact Scale with an intention-to-treat analysis. Secondary objective outcome measures were changes in balance, gait, grip strength, and cognition. Blinded assessments were performed at baseline, postintervention, and at 3- and 6-month follow-up. Results—: One hundred twenty-three participants were assigned to rhythm-and-music therapy (n=41), horse-riding therapy (n=41), or control (n=41). Post-intervention, the perception of stroke recovery (mean change from baseline on a scale ranging from 1 to 100) was higher among rhythm-and-music therapy (5.2 [95% confidence interval, 0.79–9.61]) and horse-riding therapy participants (9.8 [95% confidence interval, 6.00–13.66]), compared with controls (−0.5 [−3.20 to 2.28]); P =0.001 (1-way ANOVA). The improvements were sustained in both intervention groups 6 months later, and corresponding gains were observed for the secondary outcomes. Conclusions—: Multimodal interventions can improve long-term perception of recovery, as well as balance, gait, grip strength, and working memory in a mixed population of individuals in late phase after stroke. Clinical Trial Registration—: URL: http//www.ClinicalTrials.gov. Unique identifier: NCT01372059. Abstract : Supplemental Digital Content is available in the text.